Conductive MOFs. Issue 2 (May 2020) - Li, Wen-Hua; Deng, Wei-Hua; Wang, Guan-E; Xu, Gang
Highlights: The latest progress of conductive MOFs, including electronically and proton-conductive MOFs is summarized. The emerged new conductive MOFs and a variety of new electric-related applications are highlighted. The great challenges and opportunities for further development of conductive MOFs are pointed out. Abstract: Metal-organic frameworks (MOFs) / porous coordination polymers (PCPs) have emerged as a new family of conductive solid materials with outstanding performances in a wide variety of applications, including fuel cells, batteries, supercapacitors, catalysts, sensors, electronics, thermoelectrics, and spintronics. Only in past 10 years, novel strategies have been developed, which allowed for the rational design of both electronically and proton-conductive MOFs. In this review, the recent progress of MOF-based electronic and protic conductors, including materials preparations, conductivity measurements, conductive mechanisms, and applications is summarized and highlighted. Besides, the important breakthroughs of the MOF-based conductors for charge and proton transport, as well as the current status and challenges in this arena are elaborated. Graphical abstract: Image, graphical abstract